Feeding experiment using uniformly 13C-labeled α-linolenic acid supports the involvement of the decarboxylation mechanism to produce cis-jasmone in Lasiodiplodia theobromae. Issue 12 (2nd December 2019) - Matsui, Ryo; Takiguchi, Kisumi; Matsuda, Kazuhiko; Takahashi, Kosaku; Matsuura, Hideyuki
ABSTRACT: In our previous report, it was found that Lasiodiplodia theobromae produced cis -jasmone via partially utilizing the biosynthetic pathway of JA. A feeding experiment using uniformly 13 C-labeled α-linolenic acid, which was added to the culture media of the fungus, strongly supported that the fungus produced CJ via the decarboxylation step of the biosynthetic pathway.